Delimitation, Fisheries and Marine Scientific Research: Three Aspects of the Exclusive, Economic Zone Problematique in the Eastern Caribbean with Particular Reference to Trinidad and Tobago - Gray, Arthur (My University, 1988)
The introduction, on a global scale, of the Exclusive Economic zone:. (EEZ) regime, has presented coastal states with an extended range of opportunities with respect to the incorporation of extended areas of hydrospace and their resources—living and nonliving—into their economic and wider national security concerns. The fact that these opportunities are also viewed as challenges^ serves to underscore the point that there are certain problems associated with these opportunities which it was sought to enshrine in 'positive law» d ring the protracted and often acrimonious negotiating sessions that constituted the Third United Nations Conference On The Law Of The Sea. This thesis is devoted to an exploration of three problem-areas which, in their present form, have arisen as a direct result of the introduction of the EEZ regime. This exploration is conducted in the particular context of that arc of small, tightly packed and resource-deficient island states and territories that constitute the Eastern Caribbean sub-region with particular attention being given to the Trinidad and Tobago situation. While the range of management problems posed by the introduction of the EEZ regime were already discernible under earlier, more restricted ocean regimes, this innovation in international law has considerably amplified these problems while, at the same time, increasing national expectations with respect to the garnering of ocean-based resources. The problem-areas examined in this thesis are delimitation of maritime boundaries, fisheries and marine scientific research. In each case, the findings serve to emphasize the almost intractable nature of the EEZ problematique in the Eastern Caribbean and suggest the inappropriateness or inadequacy of this regime in the context of this sub-region.
Keywords: Economic conditions; Economic policy